Diagnosis of Sarcocystis cruzi, Neospora caninum, and Toxoplasma gondii infections in cattle - Moré, Gastón Andrés (2008)
The aim of the study was to diagnose Sarcocystis sp. infections in cattle and to detect coinfections by Toxoplasma gondii and/or Neospora caninum. Blood, diaphragm, esophagus, and myocardium from 90 beef cattle from Argentina were collected. Histopathological, immunohistochemical, polymerase chain reaction assays, and direct microscopical examination were carried out. Sarcocysts from myocardium were measured and counted. Indirect fluorescent antibody test (IFAT) for the three protozoans was performed. Sarcocystis cruzi sarcocysts were found in 100% of myocardium samples. Sarcocysts per gram ranged from 8 to 380 with higher values found in adult cattle (p < 0.001). T. gondii and N. caninum were not detected by immunohistochemistry. T. gondii DNA was found in myocardium of 2/20 seropositive animals, while N. caninum DNA was not found. Antibodies against S. cruzi were detected in all samples, those against N. caninum in 73% and against T. gondii in 91% of the samples (IFAT titer ≥25). It is concluded that serology by IFAT is a suitable method to diagnose these protozoan infections due to its specific IgG detection; therefore, IFAT may be a useful tool to evaluate the impact of each protozoan infection in coinfected animals.